Approaches to Higher Education Innovation in the Context of Industrial Revolution 4.0 - Huy, Nguyen Quynh; Vinh Trien, Le (VNU Journal of Science: Policy and Management Studies; Vol 36 No 2DO - 10.25073/2588-1116/vnupam.4231, 2020)
The Industrial Revolution 4.0 has brought about many changes including the higher education system. The main problem is how the education system could adapt to change and promote social innovation. This paper aims to describe the necessary changes and adjustments made in the education system, thereby better meeting the requirements of Industry 4.0, and creating a competitive education system, contributing to socio-economic development. With the research method based on the synthesis of documents, the research results show that, in the context of Industry Revolution 4.0 and the complexity of globalization, the philosophy in educational innovation needs to be changed so that universities can contribute more to society and enhance academic liberalization. Students need to master the knowledge and skills such as critical thinking and problem solving, communication and collaboration, creativity and innovation. In addition, literacy skills related to digital including information and communication knowledge are also important. Students should have access to knowledge based on diversity; and be ready to incorporate new knowledge that brings about positive changes, gradually fighting against injustice, lack of democracy and human rights, fostering an open society where voices are heard; and become responsible citizens. In addition, open learning platforms need to be considered by universities and teachers in deciding how to organize education and learning in the 4.0 Industrial Revolution era.